A Unique Presentation of Amniotic Band Syndrome: A Newborn With a Tail - Carla Brown MD; Megan Baber DO; Gwenevere White MD (SAGE Publishing, 2022)
A 1-day-old late preterm, small-for-gestational-age female presented with a caudal appendage-a rare finding-and abnormalities in all 4 limbs most consistent with amniotic band syndrome. The caudal appendage was lateral to midline, measured 3 cm × 0.5 cm, and had no bony abnormalities or spinal cord tethering. Limb abnormalities consisted of brachydactyly, oligodactyly, and syndactyly. Renal and head ultrasounds and an echocardiogram were normal. Chromosomal microarray showed deletion of EPHA3 , which is not associated with a known phenotype. The multidisciplinary approach of managing this infant with the rare finding of a caudal appendage and limb abnormalities is presented.